Comparison of Acne Degree among Users of Disposable and KN95 Masks - Asrinawaty, Andi Nur; Salman, Mohammad; Sofyan, Asrawati (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Maskne is a variant of acne that arises from wearing a mask. One factor that influences the incidence of maskne is the type of mask. Purpose: To compare the degree of acne vulgaris in disposable and KN95 mask wearers. Methods: This research was a cross-sectional descriptive study. The sample used was 444 people with acne vulgaris due to the use of disposable and KN95 masks. Acne vulgaris is classified based on the degree of acne. Data were analyzed bivariately using the Chi-square test. Result: This study shows no significant difference between the type of mask and the incidence of acne vulgaris (p = 0.70,p> 0.05). Conclusion: There is no difference in the degree of acne vulgaris in the incidence of maskne in individuals wearing disposable and KN95 masks.